Desenvolvimento, caracterização físico-química e avaliação sensorial de suco de jabuticaba (Myrciaria jaboticaba (Vell) Berg) - Natalia de Carvalho Teixeira (2011)
Jabuticaba is a tropical fruit with high nutritional and sensory value. It is believed to play an important role in the prevention of many oxidative and inflammatory diseases. Since most of these compounds are found in the peel, it should be searched alternatives to the full utilization of the fruit, as the development of a juice obtained from the jabuticaba aqueous extract. This study aimed to develop a juice from the aqueous extract of jabuticaba and to characterize it as the physical-chemical aspects and on the consumer acceptance, taking into account information about allegations of health benefit. The jabuticaba extracts were prepared submitting the fruit to heat treatment followed by mechanical treatment for the extraction of phenolic compounds, with subsequent filtration and pasteurization. It was tested different processing times to obtain two extracts with a high content of phenolic compounds without compromising its flavor. The extracts selected were those processed for 15 seconds (extract A) and 45 seconds (extract B). A commercial jabuticaba juice not ready to drink (extract C) was also studied. The extracts A, B and C presented a total phenolic content of 3.87, 5.32 and 2.92 g/L, a tannin content of 2.11, 2.41, and 1.40 g L, concentration of anthocyanins monomeric of 177.11, 99.28 and 10.97 mg/L and a contribution of polymeric anthocyanins to color of 30.07, 39.88 and 90.28% respectively. The sensory analysis of the two juices experimentally developed from extracts A and B (juices A e B) and the commercial juice samples (juice C) revealed that none of the experimentally juices (A and B) was in the area of rejection of the hedonic scale, while the juice C had notes on the area of rejection to the attribute of flavor. The presence of information positively influenced the acceptance and purchase intent of juices A and B (the best accepted) and negatively influenced the acceptance and purchase intent of juice C.